2013
DOI: 10.1590/s0085-56262013000100013
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in the composition of ant assemblages (Hymenoptera, Formicidae) on trees in the Pantanal floodplain, Mato Grosso do Sul, Brazil

Abstract: One of the main challenges in the study of insect communities is to explain what determines species diversity and how it occurs. Many ecological factors have been reported to affect the richness and composition of species in biological communities and different ecological and environmental factors can structure ant communities on different spatial scales (Kaspari & Weiser 1999; Kneitel & Chase 2004). In the wetlands of the Pantanal, Mato Grosso do Sul, Brazil, dry and rainy seasons alternate annually. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
(28 reference statements)
1
18
0
3
Order By: Relevance
“…Ant species richness in this study is similar to other studies in the Pantanal (Ribas & Schoereder, 2007;Marques et al, 2010;Marques et al, 2011;Silva et al, 2013;Soares et al, 2013). Wilson (1987) was the first to show that periodically flooded Peruvian Amazon forests had more species than dry forests.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Ant species richness in this study is similar to other studies in the Pantanal (Ribas & Schoereder, 2007;Marques et al, 2010;Marques et al, 2011;Silva et al, 2013;Soares et al, 2013). Wilson (1987) was the first to show that periodically flooded Peruvian Amazon forests had more species than dry forests.…”
Section: Discussionsupporting
confidence: 90%
“…participate in most ecological processes and have complex social behaviors and a variety of strategies for survival (Adis et al, 2001;Battirola et al, 2005, Castilho et al, 2005Santos et al, 2008;Silva et al, 2013;Soares et al, 2013). In an attempt to associate habitat complexity with the role played by ants in tropical ecosystems of the Pantanal, we tested the interaction between the vegetation mosaic and the distribution and richness of the edaphic ant community in the Pantanal in Brazil.…”
mentioning
confidence: 99%
“…This predominance was observed by Battirola et al (2005) in the Pantanal of Poconé, MT, Corrêa et al (2006), Soares et al (2013) in the Pantanal of Mato Grosso do Sul, and by Castaño-Meneses (2014), in a dry tropical forest in Mexico. For Ribas et al (2003), dominance behavior in ants can be observed according to the heterogeneity of host plants and availability of resources.…”
Section: Discussionmentioning
confidence: 87%
“…In A. phalerata, Solenopsis Westwood, 1840 and Camponotus Mayr, 1861 predominated (Battirola et al, 2005). Pheidole, Camponotus and Ectatomma Smith, 1868 were the most diverse genres in trees in flooded and nonflooded areas in the Pantanal de Miranda, MS (Soares et al, 2013). Pheidole, Ectatomma and Camponotus were the most diverse groups in clumps of dry matter in the Pantanal, MS (Côrrea et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation